Reviews of Physiology, Biochemistry and Pharmacology 161 - Amara, Susan G.; Bamberg, Ernst; Fleischmann, Bernd K.; Gudermann, Thomas; Jahn, Reinhard; Lederer, William J.; Lill, Roland; Nilius, Bernd; Offermanns, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Contents: F. Schweda and A. Kurtz: Regulation of Renin Release by Local and Systemic Factors M. Krauss and V. Haucke: Shaping Membranes for Endocytosis B.M. Jockusch and P.L. Graumann: The Long Journey: Actin on the Road to Pro- and Eukaryotic Cells B. Colsoul, R. Vennekens and B. Nilius: Transient Receptor Potential (TRP) Cation Channels in Pancreatic ß cells
Keywords: Medicine; Human physiology; Toxicology; Biomedicine; Human Physiology; Pharmacology/Toxicology.